Assessment of Root Surface Areas of Maxillary Permanent Teeth in Thai Patients with Complete Unilateral Cleft Lip and Palate Using Cone Beam Computed Tomography - Naowarat Saenjandee (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
The purpose of this present investigation is to assess and compare the root surface areas (RSA) of the maxillary permanent teeth between the cleft and the non-cleft sides in Thai patients with complete unilateral cleft lip and palate (UCLP) using CBCT. 216 CBCT images of maxillary permanent teeth from 20 Thai patients with UCLP were used to construct three-dimensional (3-D) tooth models with the Mimics Research 15.01 software. The cemento-enamel junction (CEJ) was identified, and the RSA of each tooth type was calculated automatically by the 3-Matic Research version 7.01 software. The medians of root surface areas of each tooth type from cleft and non-cleft sides were compared using the non-parametric Wilcoxon matched pairs signed rank test (P < 0.05). The results showed the medians of the root surface areas of maxillary central incisors, maxillary canines, first premolars, second premolars, first molars on the cleft side in Thai complete UCLP were significantly less than those on the non-cleft side. The median of the root surface areas of the four remaining maxillary lateral incisors on cleft side was smaller than on non-cleft side but no statistically significant difference. In summary, Root surface areas of maxillary permanent teeth were less on the cleft side than those on the non-cleft side.